(untitled) (Journal of Governance and Development (JGD), 2014)
Since its initial establishment, ASEAN aspires to realize the unity of Southeast Asia, and expand its membership. At the same time, ASEAN faces new problems with the expansion of membership due to increased responsibilities and potential internal disputes such as border issues, illegal labor migration, and environmental issues. ASEAN leaders agreed to have a commitment to create One Caring and Sharing Community in 2015, five years earlier than planned in Kuala Lumpur in 1997, and to disseminate to the people of ASEAN to have the â€œwe feeling.â€ For the next ASEAN Community will be colored by achievement of cooperation, solidarity, together against poverty, and enjoy a sense of security, increased awareness of environmental hygiene, including human security. Through this study will be see how the cultural linkages become social capital. In which social capital derive from culture values traced from the respective involved members to form a new power.